EFEKTIFITAS TEKNIK CLOZE UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN BAGI ANAK KESULITAN BELAJAR - Aminah Salim, Zulmiyetri, Ardisal (Universitas Negeri Padang, 2013)
The researcher begins with the observation in Indonesian learning in class IV Elementary School 05 Bandar Buat Padang about reading comprehension, the student’s having difficulty in reding comprehension. Thus giving researchers an alternative cloze technique to improve reading comprehension ability for children with lerarning difficulties. This research uses a approach Quasi Ekperiment with design Pre-test and post-test group design. The subjects were totaling four people. Collecting data in this research using a written essay test as many as 15 pieces. And the data obtained were analyzed using the Mann Whitney U test. These results Uhit> Utab at the 95% significance level or alpha = 0.05 obtained Utab = 0 at n = 4. Meaning that Ha is accepted and Ho is rejected, it is proved that the cloze technique effective for improving reading comprehension for children learning difficulties in class IV Elementary School 05 Bandar Buat Padang.